The Sno Oncogene Antagonizes Wingless Signaling during Wing Development in Drosophila. - Quijano, J.C.; Stinchfield, M.J.; Zerlanko, B.; Gibbens, Y.Y.; Takaesu, N.T.; Hyman-Walsh, C.; Wotton, D.; Newfeld, S.J. (PLoS ONE, 2010)
The Sno oncogene (Snoo or dSno in Drosophila) is a highly conserved protein and a well-established antagonist of Transforming Growth Factor-beta signaling in overexpression assays. However, analyses of Sno mutants in flies and mice have proven enigmatic in revealing developmental roles for Sno proteins. Thus, to identify developmental roles for dSno we first reconciled conflicting data on the lethality of dSno mutations. Then we conducted analyses of wing development in dSno loss of function genotypes. These studies revealed ectopic margin bristles and ectopic campaniform sensilla in the anterior compartment of the wing blade suggesting that dSno functions to antagonize Wingless (Wg) signaling. A subsequent series of gain of function analyses yielded the opposite phenotype (loss of bristles and sensilla) and further suggested that dSno antagonizes Wg signal transduction in target cells. To date Sno family proteins have not been reported to influence the Wg pathway during development in any species. Overall our data suggest that dSno functions as a tissue-specific component of the Wg signaling pathway with modest antagonistic activity under normal conditions but capable of blocking significant levels of extraneous Wg, a role that may be conserved in vertebrates.